12OHJA, 12OGlcJA, and JA-l-Val as airborne MeJA metabolites. Issue 9 (2nd September 2019) - Oki, Katsunari; Masimbula, Rishni; Miyawaki, Kanji; Takata, Yusuke; Takahashi, Kosaku; Matsuura, Hideyuki
ABSTRACT: It has been reported that airborne methyl jasmonate (MeJA) was metabolized into jasmonic acid (JA) and jasmonoyl isoleucine (JA-l -Ile). In this report, jasmonoyl valine (JA-l -Val), 12-hydroxy JA (12OHJA), and 12-glucosyloxy JA (12OGlcJA) were identified as metabolites originating from airborne MeJA using tomato ( Solanum lycopersicum ). Furthermore, the preferable conversion of (-)-MeJA (natural form) into 12OHJA, 12OGlcJA, JA-l -Ile, and JA-l -Val was observed.